Hyperbaric oxygen therapy improves angiogenesis and bone formation in critical sized diaphyseal defects. Issue 4 (April 2015) - Grassmann, JP; Schneppendahl, J; Hakimi, AR; Herten, M; Betsch, M; Lögters, TT; Thelen, S; Sager, M; Wild, M; Windolf, J; Jungbluth, P; Hakimi, M
Abstract: Besides the use of autologous bone grafting several osteoconductive and osteoinductive methods have been reported to improve bone healing. However, persistent non‐union occurs in a considerable number of cases and compromised angiogenesis is suspected to impede bone regeneration. Hyperbaric oxygen therapy (HBO) improves angiogenesis. This study evaluates the effects of HBO on bone defects treated with autologous bone grafting in a bone defect model in rabbits. Twenty‐four New‐Zealand White Rabbits were subjected to a unilateral critical sized diaphyseal radius bone defect and treated with autologous cancellous bone transplantation. The study groups were exposed to an additional HBO treatment regimen. Bone regeneration was evaluated radiologically and histologically at 3 and 6 weeks, angiogenesis was assessed by immunohistochemistry at three and six weeks. The additional administration of HBO resulted in a significantly increased new bone formation and angiogenesis compared to the sole treatment with autologous bone grafting. These results were apparent after three and six weeks of treatment. The addition of HBO therapy to autologous bone grafts leads to significantly improved bone regeneration. The increase in angiogenesis observed could play a crucial role for the results observed. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:513–520, 2015.